2020
DOI: 10.1080/21678421.2020.1797090
|View full text |Cite
|
Sign up to set email alerts
|

The Edinburgh Cognitive and Behavioral ALS Screen (ECAS) in frontotemporal dementia

Abstract: Objectives: To examine the usefulness of the Edinburgh Cognitive and Behavioral Amyotrophic Lateral Sclerosis (ALS) Screen (ECAS) as a cognitive screening tool for the detection of behavioral variant frontotemporal dementia (bvFTD). A secondary aim was to determine whether people with FTD combined with ALS (ALS-FTD) exhibit a similar ECAS profile to that of people with bvFTD alone. Methods: Patients with ALS-FTD and bvFTD and healthy controls were recruited. Participants were administered the ECAS, which compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…By assessing executive functioning, the ALS-CBS™-PhV can furthermore be feasible for testing patients with frontotemporal dementias or other motor diseases possibly presenting with a dysexecutive profile (e.g., extra -pyramidal disorders) — as shown for another MND-specific I-level neuropsychological tool, the Edinburgh Cognitive and Behavioral ALS Screen [ 20 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By assessing executive functioning, the ALS-CBS™-PhV can furthermore be feasible for testing patients with frontotemporal dementias or other motor diseases possibly presenting with a dysexecutive profile (e.g., extra -pyramidal disorders) — as shown for another MND-specific I-level neuropsychological tool, the Edinburgh Cognitive and Behavioral ALS Screen [ 20 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…From an experimental standpoint, the ALS-CBS™-PhV may allow large-scale epidemiological studies on FT disorders in MND patients [23] and facilitate follow-ups in clinical trials [4], specifically when combined with the available, self-administered ALS Functional Rating Scale -Revised [28]. By assessing executive functioning, the ALS-CBS™-PhV can furthermore be feasible for testing patients with frontotemporal dementias or other motor diseases possibly presenting with a dysexecutive profile (e.g., extra-pyramidal disorders) -as shown for another MND-specific I-level neuropsychological tool, the Edinburgh Cognitive and Behavioral ALS Screen [20,32].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of impairment on the ECAS in the bvFTD group in our sample (94%) was similar to what has been previously reported (91%). 13 The posterior functions composite score (Memory and Visuospatial domains; sensitivity 97% and specificity 96%) was the most effective measure at detecting AD when compared to healthy controls. Although the abnormality -1581 cut-off of 88 of the ACE-III had a slightly higher sensitivity (96%) than the ECAS Total Score (sensitivity 94% and specificity 96%), it had a much lower specificity (86%) at detecting AD.…”
Section: Discussionmentioning
confidence: 90%
“…[10][11][12] A recent study demonstrated that both bvFTD with and without ALS were impaired on the ECAS against a healthy control group. 13 The study showed evidence of convergent validity with four standard neuropsychological tests of naming, spelling, cognitive inhibition (executive function) and social cognition. However, the study did not investigate the clinical utility of the test by validating performance against comprehensive clinical neuropsychology assessment or against more routinely used brief cognitive assessment/screening measures.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation